Antagonism Between Saturated and Unsaturated Fatty Acids in ROS Mediated Lipotoxicity in Rat Insulin-Producing Cells - Wiebke Gehrmann; Wiebke Würdemann; Thomas Plötz; Anne Jörns; Sigurd Lenzen; Matthias Elsner (Cellular Physiology and Biochemistry, 2015)
Background/Aims: Elevated levels of non-esterified fatty acids (NEFAs) are under suspicion to mediate β-cell dysfunction and β-cell loss in type 2 diabetes, a phenomenon known as lipotoxicity. Whereas saturated fatty acids show a strong cytotoxic effect upon insulin-producing cells, unsaturated fatty acids are not toxic and can even prevent toxicity. Experimental evidence suggests that oxidative stress mediates lipotoxicity and there is evidence that the subcellular site of ROS formation is the peroxisome. However, the interaction between unsaturated and saturated NEFAs in this process is unclear. Methods: Toxicity of rat insulin-producing cells after NEFA incubation was measured by MTT and caspase assays. NEFA induced H2O2 formation was quantified by organelle specific expression of the H2O2 specific fluorescence sensor protein HyPer. Results: The saturated NEFA palmitic acid had a significant toxic effect on the viability of rat insulin-producing cells. Unsaturated NEFAs with carbon chain lengths >14 showed, irrespective of the number of double bonds, a pronounced protection against palmitic acid induced toxicity. Palmitic acid induced H2O2 formation in the peroxisomes of insulin-producing cells. Oleic acid incubation led to lipid droplet formation, but in contrast to palmitic acid induced neither an ER stress response nor peroxisomal H2O2 generation. Furthermore, oleic acid prevented palmitic acid induced H2O2 production in the peroxisomes. Conclusion: Thus unsaturated NEFAs prevent deleterious hydrogen peroxide generation during peroxisomal β-oxidation of long-chain saturated NEFAs in rat insulin-producing cells.